Prevalence of prescription opioid use during pregnancy in eight US health plans during 2001–2014. Issue 11 (7th July 2021) - Pocobelli, Gaia; Dublin, Sascha; Bobb, Jennifer F.; Albertson‐Junkans, Ladia; Andrade, Susan; Cheetham, T. Craig; Salgado, Gladys; Griffin, Marie R.; Raebel, Marsha A.; Smith, David; Li, De‐Kun; Pawloski, Pamala A.; et al.
Abstract: Purpose: To estimate prevalence of prescription opioid use during pregnancy in eight US health plans during 2001–2014. Methods: We conducted a cohort study of singleton live birth deliveries. Maternal characteristics were ascertained from health plan and/or birth certificate data and opioids dispensed during pregnancy from health plan pharmacy records. Prevalence of prescription opioid use during pregnancy was calculated for any use, cumulative days of use, and number of dispensings. Results: We examined prevalence of prescription opioid use during pregnancy in each health plan. Tennessee Medicaid had appreciably greater prevalence of use compared to the seven other health plans. Thus, results for the two groups were reported separately. In the seven health plans (n = 587 093 deliveries), prevalence of use during pregnancy was relatively stable at 9%–11% throughout 2001–2014. In Tennessee Medicaid (n = 256 724 deliveries), prevalence increased from 29% in 2001 to a peak of 36%–37% in 2004–2010, and then declined to 28% in 2014. Use for ≥30 days during pregnancy was stable at 1% in the seven health plans and increased from 2% to 7% in Tennessee Medicaid during 2001–2014. Receipt of ≥5 opioid dispensings during pregnancy increased in the seven health plans (0.3%–0.6%) and Tennessee Medicaid (3%–5%) during 2001–2014. Conclusion: During 2001–2014, prescription opioid use during pregnancy was more common in Tennessee Medicaid (peak prevalence in late 2000s) compared to the seven health plans (relatively stable prevalence). Although a small percentage of women had opioid use during pregnancy for ≥30 days or ≥ 5 dispensings, they represent thousands of women during 2001–2014.